2017
DOI: 10.1371/journal.pmed.1002224
|View full text |Cite
|
Sign up to set email alerts
|

Haemolysis in G6PD Heterozygous Females Treated with Primaquine for Plasmodium vivax Malaria: A Nested Cohort in a Trial of Radical Curative Regimens

Abstract: BackgroundRadical cure of Plasmodium vivax malaria with 8-aminoquinolines (primaquine or tafenoquine) is complicated by haemolysis in individuals with glucose-6-phosphate dehydrogenase (G6PD) deficiency. G6PD heterozygous females, because of individual variation in the pattern of X-chromosome inactivation (Lyonisation) in erythroid cells, may have low G6PD activity in the majority of their erythrocytes, yet are usually reported as G6PD “normal” by current phenotypic screening tests. Their haemolytic risk when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
123
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(127 citation statements)
references
References 18 publications
2
123
0
2
Order By: Relevance
“…Thus, asymptomatic individuals often remain unaware of their G6PD genotype status and screening for the G6PD genotype before using HbA1c to diagnose T2D may be warranted in populations or ethnic groups where G6PD deficiency is common. Similarly, a recent study identified a significant hemolytic risk in women heterozygous for the G6PD Mahidol variant when treated with primaquine who were not detected by current screening methods [ 42 ]. Rarer hematologic conditions that reduce erythrocyte lifespan, e.g., hereditary hemolytic anemias, hereditary spherocytosis, and hemoglobinopathies have also been shown to lower HbA1c [ 9 , 43 ], and should also be considered before using HbA1c in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, asymptomatic individuals often remain unaware of their G6PD genotype status and screening for the G6PD genotype before using HbA1c to diagnose T2D may be warranted in populations or ethnic groups where G6PD deficiency is common. Similarly, a recent study identified a significant hemolytic risk in women heterozygous for the G6PD Mahidol variant when treated with primaquine who were not detected by current screening methods [ 42 ]. Rarer hematologic conditions that reduce erythrocyte lifespan, e.g., hereditary hemolytic anemias, hereditary spherocytosis, and hemoglobinopathies have also been shown to lower HbA1c [ 9 , 43 ], and should also be considered before using HbA1c in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of persons residing in the community have a primary (Grade 1-6) or secondary (Grade 7-9) education and 81% of those 15 years or older are literate [18]. [15]. Only quantitative tests can identify G6PD deficient females with activity levels between 30-70% [13,19].…”
Section: Study Sitesmentioning
confidence: 99%
“…According to the WHO, G6PD point-of-care tests must be able to detect G6PDd in males with less than 30% of enzymatic activity, and have test sensitivity of at least 95% to guide primaquine treatment [4,13]. Despite positive results from laboratory settings, there is still insufficient data to determine if the CareStart™ RDT could achieve the WHO required thresholds for test sensitivity and negative predictive values, when the test is performed in field settings by the health care workers (HCWs) and/or village malaria workers (VMWs) [15]. Given the potential risks associated with misdiagnosed G6PD status, the use of G6PD RDT in a community setting will require community engagement and a careful assessment of risks [13].…”
Section: Introductionmentioning
confidence: 99%
“…The use of PMQ for radical cure is complicated by a few factors, including adherence to a 14-day course, commonly observed side effects such as abdominal pain and, specifically in G6PD-deficient individuals, the risk of drug-induced haemolysis [9][10][11][12]. TQ provides radical cure in a single dose, improving adherence, but has not yet been implemented widely since receiving approval from the US Food and Drug Administration (FDA) in 2018 [13].…”
Section: Introductionmentioning
confidence: 99%